Prevalence of folic acid supplement consumption: pre-conceptionally and during first trimester of pregnancy - Thakur, NK; Kumari, N; Roy, A; Yadav, BK (Devdaha Medical Journal, 2025)
Introduction: Folic acid deficiency causes congenital abnormalities and neural tube defects (NTDs) in fetus, newborn, as well as, anemia and peripheral neuropathy in mothers. Its supplementation is crucial both before and during pregnancy, therefore, ideally started before conception. This study aims to assess the prevalence of folic acid supplementation and its association along with other factors with congenital anomalies among pregnant woman visiting a tertiary care centre. Methods: This was a cross-sectional study conducted in 215 pregnant women presenting to department of obstetrics inpatient department, within 6 months duration of Devdaha Medical College and Research Institute, Rupandehi, Nepal. Data regarding demographics, socioeconomic status, obstetrics, folic acid supplementation status were recorded. The data was analyzed in SPSS v16. Results: A majority of the mothers were of age 15-25 years (52.6%), rural areas (58.1%), had one child (43.3%) and secondary education (46%). Pregnancy was intentional in 80% and 74.9% did not have pre-conceptional health visit. Folic acid supplementation prevalence in pregnant women was 50.7%, among which its pre-conceptional and first trimester intake was 7 and 43.7%, respectively. Similarly, the prevalence of congenital anomalies and preterm delivery was 7% and 16.7% respectively. There was association of maternal residence, alcohol consumption, period of gestation and fetal factors such as weight, twin birth with congenital anomalies. Conclusion: The prevalence of folic acid supplementation, preterm delivery and congenital anomaly was 50.7%, 7% and 16.7% respectively. Congenital anomaly was not neither significantly associated with folic acid supplementation nor socio demographic factors of mother. It was associated with alcohol consumption and comorbidities of mother.